2022
DOI: 10.3389/fimmu.2022.829923
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pattern-Recognition Receptor Signaling by HBX During Hepatitis B Virus Infection

Abstract: As a small DNA virus, hepatitis B virus (HBV) plays a pivotal role in the development of various liver diseases, including hepatitis, cirrhosis, and liver cancer. Among the molecules encoded by this virus, the HBV X protein (HBX) is a viral transactivator that plays a vital role in HBV replication and virus-associated diseases. Accumulating evidence so far indicates that pattern recognition receptors (PRRs) are at the front-line of the host defense responses to restrict the virus by inducing the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 171 publications
(224 reference statements)
0
19
0
Order By: Relevance
“…JAK/STAT consists of three components: the tyrosine kinase receptor receiving the signal, the tyrosine kinase transmitting the signal-JAK, and the transcription factor producing the effect-STAT [ 43 , 44 ]. As the downstream pathway of IFN receptors, the JAK/STAT signaling must respond rapidly to initiate ISG production [ 45 ]. HBx-mediated JAK/STAT activation plays an important role in stimulating innate immune response during HBV infection.…”
Section: Activation Of Innate Immune and Inflammatory Response By Hep...mentioning
confidence: 99%
“…JAK/STAT consists of three components: the tyrosine kinase receptor receiving the signal, the tyrosine kinase transmitting the signal-JAK, and the transcription factor producing the effect-STAT [ 43 , 44 ]. As the downstream pathway of IFN receptors, the JAK/STAT signaling must respond rapidly to initiate ISG production [ 45 ]. HBx-mediated JAK/STAT activation plays an important role in stimulating innate immune response during HBV infection.…”
Section: Activation Of Innate Immune and Inflammatory Response By Hep...mentioning
confidence: 99%
“…Intricate interactions between hepatitis viruses and TLRs have been reported with both activating and inhibiting effects ( 27 , 28 ). At steady state, in primary human hepatocytes (PHH), only the expression of TLR3, 4 and 5 could be detected at the protein level.…”
Section: Cross-talk Between Cellular Metabolism and Key Signaling Pat...mentioning
confidence: 99%
“…HCV components can also be sensed by TLRs such as HCV Core that is recognized by human TLR2 ( 34 ). Conversely, hepatitis viruses have evolved countermeasures to block TLR signaling ( 28 ). For example, the NS3/4A protease of HCV is able to cleave TRIF, the signaling adaptor recruited by TLR3 ( 35 ).…”
Section: Cross-talk Between Cellular Metabolism and Key Signaling Pat...mentioning
confidence: 99%
“…Additionally, DDX5 enhances the activation of interferon (IFN) signaling to suppress HBV replication. Activation of the JAK/STAT pathway plays a vital role in the antiviral response induced by IFN (Kong et al, 2021b;You et al, 2022). Sun et al showed that DDX5 could bind to STAT1 mRNA and modulate its translation by resolving a secondary RNA structure, namely the G-quadruplex, which is in the STAT1 mRNA 5'untranslated region (UTR) to accelerate its expression and activation to facilitate the sensitization of IFN-a signaling (Sun et al, 2022) (Figure 2).…”
Section: Ddx5mentioning
confidence: 99%
“…Because of the lack of CARDs, LGP2 is considered incompetent and inhibits RIG-I-or MDA5mediated signaling. After MAVS is activated, it further induces the sensitization of TBK1, which initiates IKK-dependent phosphorylation of NF-kB and leads to IRF3 activation to facilitate the production of inflammatory factors and IFN (You et al, 2022). Current evidence indicates that RIG-I is a viral RNA sensor with the ability to recognize the 5'-ϵ region of HBV pgRNA and induce IFN expression to inhibit infection (Figure 2) (Sato et al, 2015).…”
Section: Rig-imentioning
confidence: 99%